Muito além da fisgada: a ciência e o futebol na cobertura esportiva paraense. - SOUSA, André Laurent Souza Lopes (2020)
Reportages relating science and soccer are not frequent in the sports coverage of Pará. Understanding the causes of this problem is the main objective of this work. From the bibliographic review of sports science in soccer, the interdisciplinarity that has contributed to relevant studies for decades has not only resulted in an understanding of the sport's problems, but also in the increase of performance of soccer players and teams. Secondly, the work brings the dialogue between scientific culture (VOGT, 2003) and journalism, from the perspectives of scientific journalism (BUENO, 2009) and sports (BUENO, 2005; MALULY, 2005), in order to highlight the provocation of Messa (2005), which credits scientific journalism, the journalism sports-scientifc, with the possibility of going beyond entertainment to fan-spectator. But for this, it is necessary to understand, from semi-structured interviews, the limiting factors of the sports coverage in Pará and the reasons why science has little space. One possibility to expand the content involving science and soccer lies in the expertise and the relationship between journalists and the members of the technical commissions of football teams in Pará.